2002
DOI: 10.1002/jmri.10052
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanisms underlying transient T2 normalization in longitudinal studies of ischemic stroke

Abstract: Purpose: To determine if the phenomenon of transient normalization of T2 relaxation in the subacute stage of ischemic stroke is associated with either magnetic susceptibility effects secondary to hemorrhage or changes in tissue water content. Materials and Methods:We utilized a rat model of transient, focal, cerebral ischemia. The possibility of hemorrhage was evaluated with T2*-weighted (T2*W) imaging and histology. Changes in water content were assessed by brain wet-to-dry weight.Results: Susceptibility effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…However, the reason for the subsequent T2 normalization is not fully understood. Lin and colleagues showed a strong correlation between T2 relaxation time and ex vivo determined brain tissue water content, implicating a normalization of brain edema as main cause for the T2 normalization (Lin et al, 2002a). However, in this study, T2 normalization occurred at day 4 notwithstanding that brain edema was still maximally pronounced at this time.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the reason for the subsequent T2 normalization is not fully understood. Lin and colleagues showed a strong correlation between T2 relaxation time and ex vivo determined brain tissue water content, implicating a normalization of brain edema as main cause for the T2 normalization (Lin et al, 2002a). However, in this study, T2 normalization occurred at day 4 notwithstanding that brain edema was still maximally pronounced at this time.…”
Section: Discussionmentioning
confidence: 77%
“…However, fogging is also known to occur in animal models of focal cerebral ischemia, where a transient T2 signal normalization can be observed between day 3 and day 14 after stroke onset (Lin et al, 2002b). Another animal study identified changes of the water content, but not hemorrhage as the pathophysiological correlate of T2 fogging (Lin et al, 2002a). Nevertheless, it is still not fully understood which pathophysiological changes occur during fogging, and whether or not this phenomenon might influence the correct determination of the lesion volume.…”
Section: Introductionmentioning
confidence: 97%
“…Even though T 1 -w and T 2 -w MRI have been shown to closely reflect the extent of irreversibly damaged tissue in the past, there is evidence that this correlation will not always hold in certain brain regions and at later time points (Knight et al, 1994;Neumann-Haefelin et al, 2000). Paramagnetic properties of inflammatory cells or blood degradation products, as well as regionspecific changes in water content and breakdown of macromolecular structures with influence on relaxation times, have been discussed as possible reasons for this phenomenon (Dijkhuizen et al, 1998;Lin et al, 2002a). Our own analysis showed a time-dependent accumulation of iron-containing macrophages in the region around leaky blood vessels, which led to selective T 2 * sensitivity without any influence on either T 1 or T 2 detectable at 10 weeks after MCAO (Hoehn et al, 2004;Weber et al, 2005).…”
Section: Lesion Developmentmentioning
confidence: 99%
“…T 2 increase in ischemic lesion has also been suggested to be associated with change in magnetization transfer between mobile and immobile proton pools due to structural water alteration [76-78], in which reduced bound water fraction in ischemic tissue leads to T 2 prolongation without significant change in water content. Being highly correlated with established histological and enzymatic techniques, volume with elevated T 2 in late stages has been widely used to estimate final infarct size noninvasively [79, 80].…”
Section: Mri Characterization Of Acute Strokementioning
confidence: 99%